Effects of Motor Intervention Program on Academic Skills, Motor Skills and Social Skills in Children with Autism Spectrum Disorder. - Hatipoğlu Özcan, Gülsüm; Özer, Dilara Fatoş; Pınar, Salih (Journal of Autism & Developmental Disorders, 2025)
The aim of this study was to examine the effect of motor intervention program (MIP) on autistic index, pre-academic skills, motor skills and social skills of children with Autism Spectrum Disorder (ASD). The research group consisted of a total of 34 participants between the ages of 3–6, 17 in the control group (CG) and 17 in the experimental group (EG). EG participated in the motor intervention program for 60 min a day, 2 days a week for 12 weeks. In the study, the Gilliam Autistic Disorder Rating Scale-2-Turkish Version (GARS-2 TV), Peabody Motor Development Scale-2 (PMDS-2), Pre-Academic Skills Evaluation Form (PASAF) and Social Skills Evaluation System Preschool Teacher Form (SSRS-PTF) were used. The increase in all subtests and total scores of PASAF and posttest scores obtained from PMDS-2 were found to be higher in favor of the experimental group (p < 0.05). The decrease in the stereotype and social interaction scores of GARS-2 TV and the change in the cooperation, self-control and externalization sub-dimensions of SSRS-PTF were found to be statistically significant in favor of the EG group (p < 0.05). In conclusion, it was found that MIP applied to autistic children was effective on the development of motor skills, academic skills and social skills and decreased the level of autistic index. This result shows that MIP is an effective practice that provides a favorable environment for autistic young children to develop multiple skills.